SISTEM INFORMASI PERPUSTAKAAN PADA SD NEGERI 101935 BATANG TERAP BERBASIS WEB - Ndruru, Yufita Friska; Tatti, Leonardo; Hutagalung, Estri Aprillia; Sinurat, Rinda Anastasya; Sembiring, Natalia; Jamaluddin, Jamaluddin (Universitas Methodist Indonesia, 2023)
Currently the 101935 Batang Terap publick elementary school library, especially for book borrowers, still uses a system that is still very manual, resulting in errors in the circulation of loan books because the data is not well documented. Therefore, we need a database system application that can manage and process library transaction data in an efficient manner precise and efficient. So the authors are interested and willing to research and create this techno project with the topic entitled Web-Based Library Information System at the 101935 Batang Terap Elementary School. make it easier for librarians to process borrowing and returning data and make it easier to input data, process and process data with an application to produce fast and accurate information. The library information system at the 101935 Batang Terap public elementary school was built using the Sublime text and Xampp applications. The library information system at the 101935 Batang Terap public elementary school was created to be able to provide convenience in the process of borrowing and returning books. With the existence of a library information system at the 101935 Batansg Terap public elementary school, it can assist schools in analyzing and obtaining input material in making decisions. easy to make a report to the head of the librarian.